RELATION BETWEEN LARGE COMPLIANCE (Thalassia hemprichii) AND GASTROPODA DENSITY IN NIRWANA BEACH WATERS KOTA PADANG WEST SUMATERA - Rivai Andika Pakpahan; Zulkifli Zulkifli; Syafruddin Syafruddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This study aims to determine the density level of seagrass (T. hemprichii), the type and density of gastropods associated with seagrass, and the density relationship of seagrass with gastropod density in the waters of Nirwana Beach, Padang City. Determination of sampling locations using survey methods by making observations directly to the object of research to see closely the activities at the research site. This research was conducted in March - April 2018. Gastropod samples obtained were then analyzed at the Marine Biology Laboratory. The results of measurements of water parameters in the water temperature range from 28-29o, salinity ranges from 30-31 ‰ and water pH ranges from 7-8. Sediment types namely sandy gravel with organic matter content ranging from 4.68-5.66. For seagrass densities each station 96.44-142.34 stands / m2 and for each zone ranged from 83.67 to 163.56 stands / m2. Gastropods found in 10 species. Gastropod density at each station ranges from 82-118.4 ind / m2. For each zone ranged from 68.7 to 82.08 ind / m2 with the highest density in the species Clypeomorus sp. Linear regression analysis states that the seagrass density relationship with gastropod density from the value r = 0.96 is classified as very strong. Keywords:Thalassia hemprichii, Gastropoda, Nirwana Beach Padang City